PKM PENGENALAN PENTINGNYA PERAN DIGITAL DALAM MENGENALKAN WISATA BUDAYA DAN WISATA RELIGI KASUNYATAN BANTEN - Munawaroh Munawaroh; Alamsyah Suhendi; Putri Putri; Bela Safitri; Alfin Nadiyah; Sandi Mulyadi (JIPAM : Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Digital transformation forces us to grow differently, all sectors of human life are influenced by it ranging from business, education, even in the tourism sector, it cannot be separated from digitalization. This concept is increasingly being discussed due to the Covid-19 condition, which encourages the acceleration of the digital transformation process. Introducing Indonesia through the tourism sector to attract tourists both nationally and internationally will have an impact on the community's economy. The diversity of tourist destinations in Indonesia as a heritage such as culture, nature and also artificial tourism. Indonesia has a cultural diversity spread across 37 provinces. Each tribe and region has a different cultural diversity, influenced by different geographical conditions, regions of origin and historical and religious backgrounds. This is the uniqueness and attraction of cultural and religious tourism in Indonesia. This is the uniqueness and attraction of cultural and religious tourism in Indonesia. Banten is one of the regions on the island of Java has many uniqueness and attractions to be developed into cultural and religious tourist destinations. Banten as the first area visited by Dutch colonists when they first came to Indonesia made this area cultured with culture and various Dutch heritage buildings. This adds to the distinctive cultural diversity owned by the people of Banten. Kaibon Palace, Panembahan Pangeran Ariya Mandalika, Sulthon Abul Mafakhir Mahmud Abdul Qodir (Walnut), Panembahan Abul Ma'ali, Great Mosque of Kasunyatan, Great Mosque of walnut Sultanate are cultural and religious tourism into an acculturation of local culture and Hindu-Buddhist. The history of the entry and development of Islam in Banten, then Banten has the potential to be developed into cultural and religious tourism. This devotion uses a descriptive qualitative method with a multi-disciplinary approach on the grounds that tourism is part of a very complex culture. The purpose of devotion is to get an overview of tourist and religious destinations in Banten